What makes a die-hard entrepreneur? Beyond the 'employee or entrepreneur' dichotomy - Andrew E. Burke; Felix R. FitzRoy; Michael A. Nolan (Institute for the Study of Labor (IZA), 2006)
The paper makes three contributions to the economics literature on entrepreneurship. We offer a new measure of entrepreneurship which accounts for variations in persistence in self-employment and as a result avoids the weakness of approaches which categorise an individual as an entrepreneur by observing their occupation at just one point in their career. We outline an econometric methodology to account for this approach and find that it is superior to probit/logit models which have dominated the literature. While our results indicate that this existing literature is good at explaining an individual's propensity to try self-employment, we find that entrepreneurial persistence is determined by a different model and unearth some new insights into the roles of early career experience, finance, role models, gender and the unemployment push effect.
Keywords: 330